A novel carbon tipped single micro-optrode for combined optogenetics and electrophysiology. - Dénes Budai; Attila D Vizvári; Zsolt K Bali; Balázs Márki; Lili V Nagy; Zoltán Kónya; Dániel Madarász; Nóra Henn-Mike; Csaba Varga; István Hernádi (PLoS ONE, 2018)
Optical microelectrodes (optrodes) are used in neuroscience to transmit light into the brain of a genetically modified animal to evoke and record electrical activity from light-sensitive neurons. Our novel micro-optrode solution integrates a light-transmitting 125 micrometer optical fiber and a 9 micrometer carbon monofilament to form an electrical lead element, which is contained in a borosilicate glass sheathing coaxial arrangement ending with a micrometer-sized carbon tip. This novel unit design is stiff and slender enough to be used for targeting deep brain areas, and may cause less tissue damage compared with previous models. The center-positioned carbon fiber is less prone to light-induced artifacts than side-lit metal microelectrodes previously presented. The carbon tip is capable of not only recording electrical signals of neuronal origin but can also provide valuable surface area for electron transfer, which is essential in electrochemical (voltammetry, amperometry) or microbiosensor applications. We present details of design and manufacture as well as operational examples of the newly developed single micro-optrode, which includes assessments of 1) carbon tip length-impedance relationship, 2) light transmission capabilities, 3) photoelectric artifacts in carbon fibers, 4) responses to dopamine using fast-scan cyclic voltammetry in vivo, and 5) optogenetic stimulation and spike or local field potential recording from the rat brain transfected with channelrhodopsin-2. With this work, we demonstrate that our novel carbon tipped single micro-optrode may open up new avenues for use in optogenetic stimulation when needing to be combined with extracellular recording, electrochemical, or microbiosensor measurements performed on a millisecond basis.